HOME FINANCING AND FINANCIAL STABILITY: CASE STUDY OF INDONESIA ISLAMIC BANK - Gun Indrayana, Gun
The presence of Islamic Banking further increases financial inclusion and add newly financial institution that significantly for the development of Indonesia banking system. The market share of Islamic Banks in Indonesia slightly increases, but stagnant in range of 5%. In the previous study resulted that mortgage and Islamic banking have positive relationship to financial stability. In this study, we analyze the relationship of home financing in Islamic Banks in Indonesia. This study provides empirical assessment of variables of home financing and financial stability in Islamic Banking in Indonesia, measured by z-score. For those purpose, the study used random effect regression model method to find the relationship of home financing and financial stability in Islamic Banks using bank-level data and conduct comparative analysis of Islamic Bank with Conventional Banks (using aggregate data, time series) with multiple regression model and analyze growth of home financing portfolio with mitigate the financial stability relation. The panel data covers period of March 2010 until September 2019 using quarterly-published report data from Indonesia Financial Services Authority (Otoritas Jasa Keuangan). The regression model resulted share of home financing to total financing in Islamic Banks in Indonesia has not statistically significant relation with financial stability. Increasing the property portfolio as productive asset have to be considered due to home financing have better collateral to cover the financing/credit risk and do not have significantly relation to financial stability. Comparison of home financing in Islamic Banks and Conventional Banks, resulted that home financing in conventional Banks has statistically significant relation. There is negative relation in increasing by 1 point in share mortgage loan by 1.541 point to financial stability and positive relation in increasing by 1 point in growth of mortgage loan by 0.088 to financial stability Ratio of home financing to total financing in Islamic Banks has positive relation to ROA and have statistically significant relation. Increase in 1 point of share of home financing to total financing contribute 0.034 increase in ROA of bank. The grow of share of home financing to total financing in Islamic Banks portfolio may be considered as one of asset / financing that has no relation with financial stability and has positive contribution to growth of Islamic Banks in Indonesia and its GDP. Government regulation and Internal Bank action can synergy together to grow the property sector.